Triggerable Multivalent Glyconanoparticles for Probing Carbohydrate–Carbohydrate Interactions - Won, Sangho (ACS Macro Lett, 2018)
[Image: see text] Carbohydrate–carbohydrate interactions are proposed to be biologically significant but have lower affinities than the well-studied carbohydrate–protein interactions. Here we introduce multivalent glyconanostructures where the surface expression of lactose can be triggered by an external stimulus, and a gold nanoparticle core enables colorimetric signal outputs to probe binding. Macromolecular engineering of a responsive polymer “gate” enables the lactose moieties to be presented only when an external stimulus is present, mimicking how nature uses enzymes to dynamically regulate glycan expression. Two different carbohydrate–carbohydrate interactions are investigated using this tool.